2000
DOI: 10.1089/02724570050109602
|View full text |Cite
|
Sign up to set email alerts
|

Review: Veterinary Sources of Nonrodent Monoclonal Antibodies: Interspecific and Intraspecific Hybridomas

Abstract: The generation of monoclonal antibodies from species other than rats and mice has developed slowly over the last 20 years. The advent of antibody engineering and realization of the advantages of nonmurine antibodies, in terms of their superior affinities and specificities, and their potential as components of human and veterinary therapeutics has increased their relevance recently. There have been significant advances in the development of myeloma and heteromyeloma fusion partners. This is an opportune moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 128 publications
2
22
0
Order By: Relevance
“…A panel of BoNT/A-binding recombinant scFvs was identified that were derived from the B-cell repertoire of a sheep which had been potently immunized against BoNT/A, including boosts with increasing doses of active holotoxin. Sheep were used as the genetic source of scFvs, in part because they reportedly produce higher average affinity antibodies than do rodents (10). Several sheep were immunized by various methods and were tested for antiBoNT/A titer and neutralizing activity.…”
Section: Resultsmentioning
confidence: 99%
“…A panel of BoNT/A-binding recombinant scFvs was identified that were derived from the B-cell repertoire of a sheep which had been potently immunized against BoNT/A, including boosts with increasing doses of active holotoxin. Sheep were used as the genetic source of scFvs, in part because they reportedly produce higher average affinity antibodies than do rodents (10). Several sheep were immunized by various methods and were tested for antiBoNT/A titer and neutralizing activity.…”
Section: Resultsmentioning
confidence: 99%
“…They have long been an important source of polyclonal and more recently also monoclonal antibodies [62], [63]. As a result, there is an increasing interest in raising human antibodies in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…278,283,307 The advantages of rabbit over mouse MAbs include higher affinity (probably a result of high glycosylation), 149 suitability for use on mouse tissues without special procedures, increased specificity in some cases, and less need for antigen retrieval methods. 57,132,211,313,417 Nevertheless, in a study comparing 10 rabbit MAbs with 10 mouse MAbs targeting the same protein in animal tissues, rabbit MAbs were superior for some markers, but there was no significant overall improvement in immunoreactivity. 396 Protein A and Protein G. These cell-wall components of Staphylococcus aureus (A) and group G (G) streptococcal strains 46 are used in IHC for their high affinity for the Fc portion of IgGs.…”
Section: Monoclonal and Polyclonal Antibodiesmentioning
confidence: 99%